2016
DOI: 10.1002/pssr.201600219
|View full text |Cite
|
Sign up to set email alerts
|

Direct correlation of microstructure and device performance of liquid phase crystallized Si thin film solar cells on glass

Abstract: Si thin films on glass grown by liquid phase crystallization (LPC) exhibit large grains resembling those in multicrystalline Si wafers. The present work gives direct insight into how planar defects in LPC‐Si thin films influence the device performance of the corresponding solar cells by acquiring electron‐backscatter diffraction maps and measuring solar cell parameters on the same identical positions. By this approach, it was possible to demonstrate how low scanning velocities of the laser line during the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Former experiments have shown that the crystallization parameters effect the final material quality [23]. In detail especially slow vscan improve the microstructural properties of the silicon layer.…”
Section: Figure 4: Phase Diagram For the Crystallization Of (Left) 6 mentioning
confidence: 99%
See 1 more Smart Citation
“…Former experiments have shown that the crystallization parameters effect the final material quality [23]. In detail especially slow vscan improve the microstructural properties of the silicon layer.…”
Section: Figure 4: Phase Diagram For the Crystallization Of (Left) 6 mentioning
confidence: 99%
“…So, while the material quality of the TG-1 substrate improves and the standard deviation decreases as the scanning velocity of the laser is reduced there is no specific trend observed for the cells fabricated on SLG-2 substrates. Neither the average values nor the standard deviations are affected by the crystallization velocity in stark contrast to LPC-processed devices on technical glass substrates[23]. It is likely, that the absence of this usual trend for liquid phase crystallized absorbers is caused by the expansion coefficient mismatch between substrate and silicon.…”
mentioning
confidence: 92%
“…Moreover, electron-backscatter diffraction (EBSD) probes the local crystal orientation and symmetry, and thus can provide grain-size and orientation distributions, and also allows for categorizing grain boundaries via the misorientations between neighboring grains with spatial resolutions ranging from about 10 nm when using electrontransparent lamellae up to several cm for bulk specimens (Kühnapfel et al, 2016). From the recorded EBSD patterns, also microstrain distributions within individual grains can be determined (Schäfer et al, 2016).…”
Section: Microscopic Materials and Device Propertiesmentioning
confidence: 99%
“…In Kühnapfel et al it was shown that the amount of recombination active grain boundaries can be reduced by proper crystallization parameters. However, the contribution of the absorber deposition process is unclear, yet.…”
Section: Bulk Limitationsmentioning
confidence: 99%